Analysis of PT Lhoong Setia Mining's Responsibility for Land Reclamation in the Perspective of Environmental Fiqh - Fitria Mardhatillah; Shira Thani; Fitri Maghfirah (Winaya Inspirasi Nusantara Foundation, 2024)
Mining businesses play an important role in providing real added value for national economic growth and sustainable regional development. However, the excessive exploitation of natural resources will have an impact on the sustainability of natural resources and environmental functions. Land reclamation is the responsibility of mining companies to restore post-mining environmental conditions. This study utilizes a qualitative analysis method with a comparative analysis data collection technique, namely by comparing various journals, written information from the internet, and other literature. According to Law Number 3 of 2020 regarding Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining, companies or business actors are required to carry out post-mining reclamation. As a result of field findings, PT Lhoong Setia Mining has not conducted the land reclamation process or fulfilled other obligations. This is not in line with laws, regulations, and the principles of environmental fiqh in mining land exploration.